Dynamics and acoustic energy dissipation in conical bubble collapse. (November 2015) - Navarrete, M.; Godínez, F.A.; Castellanos, F.; Mejía-Uriarte, E.V.; Naude, J.L.; Méndez, F.
Graphical abstract: Highlights: The dynamics of the collapse of a conical bubble is analysed by high-speed video. New data in image format are reported for the compression phase. The luminescence emerges mainly from two sources and is detected from two locations. The shock wave onset is identified indirectly by signal analysis via WT and STFT. The experimental data are consistent with those predicted by two classical models. Abstract: We follow the dynamics and acoustics of conical bubble collapse (CBC) in a U-tube device, to understand its associated phenomena such as: light emission, turbulence, bubble cloud formation, strong rebound pressures, shock wave emission, and liquid–gas interface behaviour. High-speed video frames linked with the waveforms acquired by piezoelectric transducers and photomultipliers during the collapse are analysed. All of the data acquisition is synchronised to the same timeline. Acoustic energy dissipation is investigated in detail by analysing the piezoelectric waveforms using Fourier transforms and wavelets. The primary experimental results demonstrate that as the compression proceeds, (a) the liquid meniscus reaches the conical zone in cavitation conditions; (b) the liquid meniscus undergoes a geometric transformation (2D to 3D), it becomes a "bulb with a nozzle", wherein the instabilities are dragged and confined inside it; (c) the nozzle is retained as part of the new meniscus that continues to push the gas pocket; and (d) both structures (bulb and gas pocket) are connected by a neck/nozzle and will eventually form a "slug". Furthermore, during the collapse, the bulb eventually becomes a bubble cloud, and the bubble structures exhibit their own expansion–contraction rate. These phenomena are widely discussed. A detailed analysis of the acquired signals yields frequencies and scales, which are associated with the onset of shock waves and its propagation, as well as the frequency bands that occur when the energy has dissipated. Good agreement was found between the experimental measurements and two different models for CBC dynamics. From the analysis of the dynamics and acoustics, we consider that various light emission mechanisms are activated during the collapse of a conical bubble, these are: thermal, chemical, and electrical in nature.